PEMBELAJARAN SENI TARI TERHADAP PERKEMBANGAN FISIK MOTORIK ANAK USIA DINI - Wisra, Okta; Mayar, Farida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Art can not be separated from human life, including for early childhood development. Besides having aesthetic value, art can also stimulate children's creativity. Early childhood education which is the forerunner to the nation's educational process seeks to develop potential in various aspects such as cognitive, language, art, moral, religion, motor, social emotional. One aspect of physical development that needs to be developed is the motor aspect of children. Early childhood motor development is as important as other aspects of development. If the child is unable to perform physical movements properly will foster insecurity and negative self-concept in doing physical movements. One form of children's motor stimulus is through dance learning, where motor development includes the development of gross motor and fine motor. The motor ability of each child is different depending on the level of maturity. Therefore, parents or teachers need to provide space and time for children to do activities that can train the child's rough muscles and provide goods and equipment for children that can be pushed, raised, thrown or carried.